Ensuring property rights under martial law - Viktoriia RIEZNIKOVA; Ivan KOSTYASHKIN; Tetiana LAHOIDA; Iryna KRAVETS; Antonina BOIKO (Revista Jurídica Portucalense, 2023)
The purpose of this article is to analyse the current state of ensuring property rights under martial law, highlighting the main groups of problems arising from it. The methodological basis of the research consists of general and special-legal methods of scientific knowledge, namely: dialectical method, systemic-structural method, logical-legal method, methods of comparison and analysis. The article provides a description of the current state and current issues arising from the provision of property rights under martial law. The proposed study provides a more comprehensive view of the picture of the provision of property rights under martial law, both with regard to individual problems of legal regulation and their interrelationship. Prospects for further research can be seen in the detailed analysis of the problems outlined in this article and the formulation of proposals for their solution in view of the current practice of law-making and law enforcement.